2021
DOI: 10.1038/s41598-021-85595-7
|View full text |Cite
|
Sign up to set email alerts
|

PLA1A expression as a diagnostic marker of BRAF-mutant metastasis in melanoma cancer

Abstract: BRAF and NRAS are the most reported mutations associated to melanomagenesis. The lack of accurate diagnostic markers in response to therapeutic treatment in BRAF/NRAS-driven melanomagenesis is one of the main challenges in melanoma personalized therapy. In order to assess the diagnostic value of phosphatidylserine-specific phospholipase A1-alpha (PLA1A), a potent lysophospholipid mediating the production of lysophosphatidylserine, PLA1A mRNA and serum levels were compared in subjects with malignant melanoma (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…For the further confirmation of these results, in our recently published study, we detailed the use of PLA1A as a marker for thre effective prediction of advanced melanoma with subcutaneous metastases following BRAF or NRAS mutation [37] . We confirmed that the upregulation of PLA1A in the serum of patients with advanced MM could represent an excellent distinguishing and diagnostic marker in BRAF/NRAS-driven melanomagenesis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For the further confirmation of these results, in our recently published study, we detailed the use of PLA1A as a marker for thre effective prediction of advanced melanoma with subcutaneous metastases following BRAF or NRAS mutation [37] . We confirmed that the upregulation of PLA1A in the serum of patients with advanced MM could represent an excellent distinguishing and diagnostic marker in BRAF/NRAS-driven melanomagenesis.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, it plays an important role in promoting or inhibiting cancer cell proliferation/migration depending on the origin and type of cancer cell, and the outcome may be associated with expression levels of PLA1A and DMKN in the tumor [ 59 , 60 ]. A literature review revealed that the field is filled with inconsistent findings that make it difficult to ascertain the roles of PLA1A and DMKN in neoplasia and immunity associated with melanoma [ 37 , 57 , 59 , 61 ]. Nonetheless, this pilot study warrants a larger analytical study in transcriptomic and post-transcriptomic levels to confirm the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study represented that DMKN levels gradually elevated during the progression of melanomagenesis, while negative DMKN expression predicted an optimistic pancreatic cancer clinical stage [7]. Additionally, the upregulation of DMKN in the advanced metastatic melanoma tissues could be an excellent diagnostic marker in BRAF/NRAS-driven melanomagenesis [11]. Interestingly, DMKN genes served as the novel oncogenes triggering VM and EMT processes during melanomagenesis [7,11].…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, the transcriptome pro ling of the EMT/VM-mediated treatment-resistant samples could be a valuable strategy for nding exceptional responders to the personalized melanoma therapy [9,10].Recently, researchers tried to nd novel VM/EMT-targeted therapeutic genes that are differentially regulated during melanomagenesis. One of the identi ed genes was a recently-reported skin-speci c gene, phosphatidylserine-speci c phospholipase A1-alpha (PLA1A) and dermokine (DMKN) that contribute to melanomagenesis by triggering the EMT signaling pathway and VM formation [11,12]. These genes can be transcriptionally used as promising biomarkers for exceptional responders in the targeted melanoma therapy [12].…”
mentioning
confidence: 99%